Электрическая модель дуги, горящей в динамическом режиме; Известия вузов. Физика; Т. 56, № 12-2 - Князьков А. Ф. Анатолий Фёдорович; Пустовых О. С. Ольга Сергеевна; Верёвкин А. В. Алексей Валерьевич; Подзывалов А. А. Андрей Александрович (2013, 2013)
Заглавие с экрана